How Five Student Characteristics Accurately Predict For-Profit University Graduation Odds - Tim Gramling (SAGE Open, 2013)
President Obama’s goal is for America to lead the world in college graduates by 2020. Although for-profit institutions have increased their output of graduates at ten times the rate of nonprofits over the past decade, Congress and the U.S. Department of Education have argued that these institutions exploit the ambitions of lower-performing students. In response, this study examined how student characteristics predicted graduation odds at a large, regionally accredited for-profit institution campus. A logistic regression predicted graduation for the full population of 2,548 undergraduate students enrolled from 2005 to 2009 with scheduled graduation by June 30, 2011. Sixteen independent predictors were identified from school records and organized in the Bean and Metzner framework. The regression model was more robust than any in the literature, with a Nagelkerke R 2 of .663. Only five factors had a significant impact on log odds: (a) grade point average (GPA), where higher values increased odds; (b) half time enrollment, which had lower odds than full time; (c) Blacks, who had higher odds than Whites; (d) credits required, where fewer credits increased odds; and (e) primary expected family contribution, where higher values increased odds. These findings imply that public policy will not increase college graduates by focusing on institution characteristics.